Assessment of functioning in Dutch primary care: Development study of a consultation tool for patients with chronic conditions and multimorbidity - Simone Postma; Henk Schers; Tom van deBelt; Kees vanBoven; Huib tenNapel; Hugo Stappers; Debby Gerritsen; Tim Olde Hartman (Wiley, 2022)
Abstract Background In primary care, a shift from a disease‐oriented approach for patients with multimorbidity towards a more person‐centred approach is needed. Aim To transform a self‐report questionnaire for patients with chronic conditions in primary care, the Primary Care Functioning Scale (PCFS), into an understandable, visually attractive and feasible consultation tool for patients and health care providers. The consultation tool consists of a web‐based version of the PCFS, which is filled in by the patient and is processed to a feedback report that summarizes and visualizes the main findings. The feedback report can be discussed with the patient to facilitate a more person‐centred conversation for patients with chronic conditions and multimorbidity in general practice. Design and Setting In this qualitative study, we developed the consultation tool by using design thinking in a participatory developmental process. Methods In the first phase, we constructed five different feedback report templates to summarize and display the results of a completed PCFS questionnaire in a series of two expert meetings with patients and general practitioners (GPs). In the second phase, we performed an exploratory qualitative interview study involving dyads of patients with chronic conditions and their practice nurses. In an iterative process, we explored their experiences with the consultation tool. Results Patients, as well as GPs, preferred a clear manner of presenting the results of the questionnaire in a feedback report. In 18 interviews with patients and practice nurses during three different interview rounds, we adjusted the feedback report and consultation tool based on the input from patients and practice nurses. After the final interview round, patients and practice nurses consented that the consultation tool was useful for having a more in‐depth consultation about functioning and patients' preferences when integrated into the regularly scheduled consultations. Conclusion We were able to develop an understandable and feasible consultation tool that is applicable in already existing chronic disease management programmes in general practice in the Netherlands. Patient or Public Contribution To increase the understandability and feasibility of the consultation tool, we collaborated with end‐users and actively involved patients, GPs and practice nurses in a participatory development process.